Heterocyclization reactions study of 3-thio and 3-thio-4-amino derivatives of 1,2,4–triazole - O. A. Bihdan; O. I. Panasenko; Ye. G. Knysh; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Scientific publications of recent years clearly demonstrate the prospects of finding new molecules among 1,2,4-triazole derivatives. The whole series of drugs, which are 1,2,4-triazole derivatives (fluconazole, ribavirin, avesstym, tryfuzol and others), are included into the practice of modern medicine, pharmacy and veterinary.